Analisis Ucapan Hukuman Ilahi Terhadap Para Imam Dalam Maleakhi 2:1-3 Yang Berimplikasi Pada Keputusan Orang Percaya - Pattinaja, Aska Aprilano; Sualang, Farel Yosua (Institut Agama Kristen Negeri Palangka Raya, 2024)
There are two groups of scholars who discuss Malachi 2:1-3 from different perspectives, namely, the divine perspective and the priestly perspective. These two views have led to the fallacy of dichotomizing the intent of the divine utterance. This article comprehensively correlates these two perspectives, which have implications for believers' decisions, based on the hermeneutic method of studying prophetic literature in the sub-genre of catastrophic prophecy. This article finds that the influence of divine punitive speech has great implications for the factors that influence believers' decisions, namely First, the Listening Factor, which discusses the decision to direct our hearing to the Word of God; Second, the Attention Factor, which discusses the decision to specifically and deliberately provide a sincere heart to fellowship and glorify God; and Third, the Honoring God's Name Factor, as an effect of the previous two factors, which makes every believer choose to honor God's name. The results of this study serve as a warning to every believer, especially to servants of God and ministers in the church as serving priests.